Estrus synchronization and artificial insemination with fresh and chilled semen in Assaf ewes - Fornazari, Raquel (2018)
This paper aims to study the efficiency of two short-term progestagen (FGA vs. MAP) + eCG treatments in estrus synchronization and artificial insemination (AI) with fresh or chilled semen in Assaf ewes fertility rate. All ewes received a subcutaneous implant of exogenous melatonin 45 days before been treated with short-term progestagens + eCG. By June 1st, ewes were divided in two groups: half was treated with an intravaginal sponge impregnated with 20 mg of FGA and the other half with an intravaginal sponge impregnated with 60 mg of MAP. Progestagen treatments lasted for 6 days. At sponge withdraw, all ewes were injected with 750 IU of eCG. Ovarian activity was assessed by plasmatic progesterone levels before and after progestagens + eCG treatment. Semen was collected by electro ejaculation and extended with Andromed® or OviXcell®. AI was performed 55 hours after eCG administration with fresh or chilled semen. During AI several factors were assessed: vagina mucosa color and lubrication, external cervical Os type, cervical mucous viscosity, semen deposition place and seminal cervix outflow. Semen was deposited as deep as possible without distress or trauma cervix mucosa. All Assaf ewes presented cyclic activity before progestagen + eCG treatments (2nd fortnight of May). Short-term progestagen + eCG treatments were equally efficient (100.0%). About 76.5% of Assaf ewes were pregnant 41 days after AI. Fertility rate was influenced by external Os type, semen deposition place and seminal cervix outflow. However, this rate was not conditioned by vaginal color or lubrication, cervical mucus viscosity, semen preservation technic and semen extender.